Role of adhesive attachments in traumatic dental injury - Basudan, Thuraya Abdulrahim; Zagzoog, Ghaida Mazen; Alshehri, Waad Amer; Alammari, Abdullah Hassan; Althaqafi, Khaled Abid; Alamri, Zahrah Ali; Alzurqi, Nada Ibrahim; Alqunfuthi, Naif Ibrahim; Alshahrani, Razan Saeed; Aldahlan, Bashayer Ghazi; Alzahrani, Rahaf Ahmed (International Journal Of Community Medicine And Public Health, 2022)
Crown root cracking is uncommon, accounting for less than 7% of irreversible damage. All the hard tissues of the teeth (crust, dentin, and cementum), as well as the pulp and periodontal ligament, are commonly involved in these complicated fractures. The care of such instances offers major biological hurdles, and success is dependent on considering a variety of regenerative, endodontic, and temporal variables. Numerous clinical investigations demonstrate that adhesive coronal attachment might be an essential therapy for fractured teeth with crown roots. Because it maintains the original tooth, this technique may save the gums and decrease the time and expense of therapy. Before considering adhesive attachments for dental fractures, several factors should be considered-the site and size of the fracture, the fracture pattern, and the position of traumatized teeth. The aim of the article was to review the role of adhesive attachments in a traumatic dental injury.